Child-education program for the reduction of health risks due to fluoride in water sources in the Chiang Mai Basin, Thailand - S. Takizawa (2018)
Groundwater is the major source of drinking water in Lamphun Province in the Chiang Mai Basin, Thailand. However, groundwater contains high fluoride up to 16mgF/L, which has caused dental and skeletal fluorosis. Although Thai Government installed RO membrane plants for the removal of fluoride from groundwater; and delivers RO-filtered bottled water that contains less fluoride than the Thai Standard of 0.7mgF/L, it was found that the urinary fluoride levels are still high among the residents. To find the major sources of fluoride intake, fluoride contents in various water sources, such as village water supply, shallow and deep groundwaters, rain water and bottled water, were measured, and the local people's behavior on water uses was recorded by interview and questionnaire study. As a result, it was found that the highest risk of fluoride ingestion comes from cooking rice with fluoride-containing water because of a lack of knowledge on fluoride sources and fluoride chemistry. To reduce the health risks arising from fluoride intake, a hands-on educational program on the sources and risks of fluoride in water was developed and implemented in the local schools. The participatory educational program promoted active involvement of schoolchildren, but it was found that the effectiveness of education varied depending on the questions we asked. Therefore, it needs to be improved by an iterative and interactive educational program. In conclusion, it was found that the benefits of providing safe drinking water using such advanced technology as RO membrane can be maximized only when it comes along with a participatory educational program on fluoride sources and health risks. © IWA Publishing 2010.